Technology Development and Job Creation in China - Nannan Lundin; Fredrik Sjöholm; He Ping; Jinchang Qian (Research Institute of Industrial Economics (IFN), 2007)
This paper examines how Science and Technology (S&T) contribute to job creation in the Chinese manufacturing sector. The ambition of transforming China into an innovation-oriented nation and the emphasis on indigenous innovation capacity building have placed Science and Technology (S&T) high on the Chinese policy agenda. At the same time, the need for job creation is pressing, both to absorb the huge supply of underemployed people, and to enable the annual 20 million new labor market entrants to find employment. We examine the relationship between S&T and job growth in the Chinese industrial sector. S&T can be expected to have both positive and negative effects on employment. For instance, new technology might increase competitiveness and enable Chinese firms to expand their labor force. On the other hand, new technology might be labor-saving, thereby enabling Chinese firms to produce more output with fewer employees. Based on a large sample of manufacturing firms in China between 1998 and 2004, we analyze how S&T affect employment growth. Our results suggest that S&T activities have no effect on job creation.
Keywords: J21; O14; O33; 330; China; Science and Technology; Job-Creation; Technischer Fortschritt; Industrielle Forschung; Innovation; Beschäftigungspolitik; China